The Lithuanian school for young mathematicians: reality and perspective - Apynis, Antanas; Stankus, Eugenijus; Šinkūnas, Juozas (Lietuvos matematikos rinkinys, 1999)
The history and survey of the activity of the Lithuanian school for young mathematicians is presented.